Information And Crime - Suleymanova Dilfuza Vaxidovna; Kuldasheva Feruza Kurdashevna; Khodjayeva Fotima Abduvaxabovna (Zien Journals, 2022)
In the years that followed, information protection problems attracted not only professionals but users of all computing techniques
Keywords: computing; information; protection; attracted